Reconstructing the Concept of Mahar through the Mubādalah Framework from a Gender Justice Perspective: Implications for Contemporary Islamic Family Law Reform - Fathul Mu'in; Relit Nur Edi; Diah Mukminatul Hasimi; Muhammad Jayus; Ikhwan Fikri (Brajamusti Publication, 2025)
This article examines mahar practices in contemporary marriage as a form of structural gender injustice embedded within Islamic family law. Extreme mahar practices whether involving excessively low or excessively high amounts not only deviate from the normative objectives of sharīʿa but also restrict women’s access to marriage, weaken their bargaining position and negotiating capacity, and perpetuate discriminatory and unjust practices within spousal relations. In this context, mahar frequently functions as a symbolic instrument of power relations that positions women in a subordinate role, rather than recognizing them as equal subjects within the marital contract. This study aims to identify the underlying roots of gender injustice in mahar practices and to formulate a conceptual reconstruction grounded in justice and reciprocity through the perspective of mubādalah. The research employs a qualitative normative library-based methodology, utilizing content, comparative, and contextual analyses. Primary sources include the Qur’an, ḥadīth, classical fiqh texts of the four Sunni schools, the Compilation of Islamic Law, and the Marriage Law, while secondary sources consist of scholarly books and peer-reviewed journal articles. The findings indicate that mahar in classical fiqh is inherently flexible and intended to honor and dignify women. A mubādalah-based mahar model reconceptualizes mahar as a symbol of reciprocity and partnership, and demonstrates potential as an instrument for Islamic family law reform aimed at preventing structural injustice and promoting family welfare through gender-responsive policies. This article therefore recommends the adoption of more gender-responsive state policies through the strengthening of family law regulations and the standardization of premarital education.